Human milk macro- and trace-elements: Simultaneous analysis in sub-milliliter amounts by ICP-MS and application to assessing acute supplementation effects - Daniela Hampel; M. Munirul Islam; Setareh Shahab-Ferdows; Lindsay H. Allen (Heliyon, 2024)
Adequate concentrations of human milk (HM) nutrients, including macro- and trace-elements, are essential for healthy growth and development of exclusively breastfed (EBF) infants. To monitor potential risk of deficiencies, and evaluate the effects of interventions like supplementation, accurate analysis is crucial. Even recent methods reporting on HM macro- and/or trace-elements describe multiple methodological approaches and the need for several milliliters. We optimized and validated a comprehensive method for simultaneous analysis of 13 macro- and trace-elements for simultaneous analysis by inductively-coupled plasma-mass spectrometry. 100–600 μL HM were microwave digested with ≤1.5 mL HNO3 (70 %). The digest was diluted to 5 % final acid concentration. He-Kinetic Energy Discrimination (KED; Na, K, P, Ca, Mg, Fe, Cu, Zn, Cr, Mo) and O2-Dynamic Reaction Cell (DRC; As, Mn, Se) modes minimized remaining interferences. Accuracy (NIST SRM 1869 infant formula; n = 15, 4 weeks) varied from 93.2 to 103 % (CV: 2.8–8.5 %) with trueness ranging from 93.9 to 104 %. Inter-day variation of a HM-pool (n = 20, 3 weeks) varied between 4.1 and 8.5 % for most elements; Cr, Mo, Mn (all<5 μg L−1) had higher variation, up to 25 %. Analyzing HM from 18 Bangladeshi mothers (2–4 months postpartum; day 1 = baseline, n = 17; day 2/3 = supplementation, n = 21 each) revealed higher concentrations for P, Ca, and Zn post-supplementation (p < 0.05, Friedman's Chi-Square Test). Na, Mg, Zn, and Se had the highest number of samples (>80 %) with concentrations below the Adequate Intake. Our method allows for simultaneous and reproducible analysis of macro- and trace-elements with concentrations ranging over 6 orders of magnitude, without the need for separate analytics and sample preparations, and requiring only sub-milliliter amounts of HM. Additional elements may be included after optimization and validation. The results from Bangladeshi HM samples indicate selective supplementation effects and concerningly low concentrations for some elements, which could adversely affect the EBF infant.